The Settlement Infrastructure of Ukrainian Stock Market: State and Directions for Reform - KOLOHOIDA, Oleksandra V.; LUKACH, Iryna V.; POIEDYNOK, Valeriia V.; BOBRYK, Volodymyr I. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019, 2020)
The research defines the concepts of clearing and clearing activity. It explores the models of the clearing institutions’ organizational structure in EU countries. It also outlines the directions for the settlement and clearing infrastructure reform based on the diversification of the settlement and clearing functions. It should ensure the integrity of the stock market, the reduction of risks, the creation of an efficient and transparent system for the execution of transactions with securities; reduction of expenses of market participants; acceleration of payment terms for operations with securities and process of registration of property rights; differentiation of responsibility at different stages of performance of transactions. The author has defined the legal status of the Financial Settlements Center as a banking institution with a special legal personality of the conducting monetary settlements under transactions concerning securities and other financial instruments, made on the stock exchange and outside the stock exchange, if payments are made according to the principle of ‘supply against payment’. The study shows the need for the universal model of settlements to serve all the exchange markets. We offer to demonopolize the market of clearing services and to provide access for international clearing institutions. We also suggest transferring the settlement function to the Central Depositary and the clearing function – to clearing institutions.